Intestinal malformation Small bowel atresia: three observations
Three observations, with different evolntion, of intestinal malformation, atre sia of the small intestine, are presented. In the first case, a jejunotransversotomy was performed, after the resection of the ileon, caceum and ascending colon. Because of the extent of the resection and the fact that the caecum was included, the intestinal zones more apt for absortion were suppressed. Perhaps it would have been beneficia